New record genus and a new species of Allodiatrype from China based on morphological and molecular characters - Peng, Ming-Kai; Zhang, Bo; Qu, Zhi; Li, Yu; Ma, Hai-Xia (Phytotaxa, 2021)
The genus Allodiatrype (Diatrypaceae, Xylariales) is reported for the first time collected in Taiyang River National Forest Park, Yunnan Province. An undescribed Allodiatrype species is described and illustrated as a new species based on a combination of morphological characteristics and sequences data of ITS, SSU and TUB2. The new species is characterized by its Y-shaped or cruciate-shaped ostiolar surface, yellowish-green to the green inner layer, and hyaline, ellipsoidal to cylindrical or elongate-allantoid ascospores. The differences between the new species and the related fungi are discussed.